Pulmonary Embolism with Floating Right Atrial Thrombus Successfully Treated with Streptokinase - Nasrin, Sahela; Salahuddin, Mohammad; Cader, Fathima Aaysha; Iqbal, Md Jabed; Nazrin, Tahera; Shafi, Masuma Jannat; Ghafoor, Nusrat (Anwer Khan Modern Medical College Journal, 2017)
Massive Pulmonary Embolism (PE) is associated with significant mortality, especially if compounded by haemodynamic instability, right ventricular dysfunction and right atrial thrombus. Thrombolysis can be lifesaving in patients with major embolism and cardiogenic shock, and accelerates the resolution of thrombus. Only three fibrinolytic agents - namely streptokinase, urokinase, and recombinant tissue plasminogen activator (Alteplase) have been approved in the treatment of PE, with studies demonstrating similar safety profiles. We report the case of a 33 year old Bangladeshi female with a history of recent ankle fracture and immobilization, who presented with massive PE, leading to cardiac arrest. Upon rapid resuscitation, urgent echocardiogram revealed right ventricular dysfunction with floating right atrial thrombus, and she was successfully treated with 1.5 million IU of Streptokinase over 2 hours as per accelerated regimen recommended by the European Society of Cardiology (ESC) guidelines, resulting in successful resolution of the right heart thrombus, and significant clinical improvement. Subsequent CT Pulmonary Angiogram confirmed the diagnosis of PE, and she was anticoagulated to a PT/INR of 2.0 to 3.0. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 60-63